Characterization of Cinnamomun Verum oil from soxhlet extraction: article - Abdul Rashid, Nur Fatin; Ismail, Norhuda (2017)
In this research, focus will be on the determination of the component and medical properties in Cinnamomun Verum. Gas Chromatography-Mass Spectrometry (GC-MS) is used to characterize the components in Cinnamomum verum and Fourier Transform Infrared Spectroscopy (FTIR) to identify the chemical structure in Cinnamomun verum. Soxhlet extractor is used to extract the essential oil using ethanol, hexane and dichlomethane solvent. Based on the result obtained, ethanol extract had the highest essential oil yield (13%) and contained high percentage of ECinnamaldehyde (55.3%). The component determined from different types of solvent is similar however the composition is varying from each sample. Others major compound in Cinnamomun verum are gurjunene(15.97%), citronelly isobutyrate(3.69%), humulane-1,6-dien-3-ol (2.11%), 1- methylpiperidine(1.27%), spathulenol (1.19%) and elemene (1.11%) based on ethanol extract. These compounds were mainly reflected in the alkane, alkene, amide, aromatic and aldehyde group. There are ten compound that was determined to exhibit therapeutic activities such as E-Cinnamaldehyde, spathulenol, elemene, caryophyllene, aromadendrene, champhene, squalene, a-pinene and aristolene. Most of the compound in the Cinnamomun verum showed antimicrobial, anti-cancer, anti-tumor, anti-oxidant and anti-inflammation properties.